I. x^{2} + 91 = 20x

II. 10y^{2} - 29y + 21 = 0

I. x^{2} + 91 = 20x => x^{2} - 20x + 91 = 0 => x^{2} - 13x - 7x + 91 = 0 =>x(x - 13) - 7(x - 13) = 0 => (x - 13) (x - 7) = 0 => x = 13, 7 II. 10y^{2} - 29y + 21 = 0 => 10y^{2} - 14y - 15y + 21 = 0 => 2y(5y - 7) - 3(5y - 7) = 0 => (5y - 7) (2y - 3) = 0 => y = 7/5, 3/2 Hence, x > y. Alternate Method: if signs of quadratic equation is - ve and +ve respectively then the roots of equation will be +ve and +ve. So, roots of first equation = x = 13, 7 So, roots of second equation = y = 7/5, 3/2 After comparing we can conclude that x > y.

- I. 2x
^{2}+ 13x + 21 = 0 II. 3y^{2}+ 34y + 63 = 0 - I. 8/(√x) + 6/(√x) = √x II. y ³- (14)
^{7/2}/(√y) = 0 - I. 6 y² + 11 y – 7= 0 II. 21 x² + 5 x – 6 = 0
- I. 35x² - 51x + 18 = 0 II. 30y² + 17y – 21 = 0
- I. 2b
^{2}- 37b + 143 = 0 II. 2a^{2}+ 15a - 143 = 0 - I. 8x² - 78x + 169 = 0 II. 20y² - 117y + 169 = 0
- I. 3p² - 17p + 22 = 0 II. 5q² - 21q + 22 = 0
- I. 35 y² + 58 y + 24 = 0 II. 21 x² + 37 x + 12 = 0
- I. 8x
^{2}- 2x – 15 = 0 II. 12y^{2}- 17y – 40 = 0 - I. 6x
^{2}- 47x + 77 =0 II. 6y^{2}- 35y + 49 = 0

More Quadratic equation Questions

×